ANALISIS KEMENANGAN JOKO WIDODO – JUSUF KALLA PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 DI KABUPATEN PELALAWAN - Eddo Guntur Pratama; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research looked at how the winning team or coalition strategy Joko Widodo - Jusuf Kalla in winning the presidential and vice presidential elections in Pelalawan in 2014. The main problem that became a phenomenon in this study is to see Pelalawan is one of the bases of the Golkar party, but in the general election of President and Vice President in 2014 was won by the pair Joko Widodo - Jusuf Kalla in the stretcher by PDI, by because it contained irregularities and because also the strategy undertaken by the winning team Jokowi - Jusuf Kalla in the general election of President and Vice President 2014. This study used qualitative methods as a means of collecting primary data proving the hypothesis is done logically and rationally through the opinions, theories or laws are accepted as true, either rejecting or supporting the research. By because the researchers used interviews with key informants know about the problems that are considered to be observed and documents that are considered important in the completion of this study. The theory used in this study is the concept of Newman and Shet, there are four options strategies as follows: Reinforcement Strategy (strengthening strategy), rationalization Strategy (rationalization strategy), Inucement Strategy (strategy persuasion), Confrontation Strategy (strategy persuasion). Judging from the figures Joko Widodo or better known as Jokowi, a phenomenal figure in a few years before the 2014 presidential election takes place. Jokowi in daily shows kesederhaannya attitude and proximity to the people judged by many observers meruapakan one of the things that factor into the increasing level of popularity and elektabilitas (desirability) community to Jokowi. Then through the role of the media, namely issues and public policy through programs of each pair of candidates try to be promoted to the public. At this time the television is no longer a tertiary goods (luxury), but almost all people in Indonesia from the middle-upper kebawa have a television, so that the issues and programs of each pair of candidates obtained directly by the people who will have an impact on the movement of opinion sesusai public with the information that people get, Based on the results of the study the researchers did that winning Jokowi-JK in the 2014 Presidential Election in Pelalawan, field-JK Jokowi Campaign Team uses a strategy of strengthening and persuasion strategies are also assisted by volunteers and media. In addition Jokowi figure is also very important in influencing the community to select the pair number two (Joko Widodo - Jusuf Kalla) in the 2014 Presidential Election and the impact on the couple's victory in the area which is known as the Golkar Party base.